(untitled) (Journal of Global Accounting, 2022)
Poor human capital development has been seen as one of the major causes of political unrest, insecurity, uprising and springing up of separatist movement in Nigeria. In the recent time, the gap emanating between the rich and the poor has stretched out a once growing middle class. Developed countries grow their middle class and improve on the economic indices by putting adequate infrastructure, (i.e. human capital development to aid the growth of small and medium enterprises). Due to the recent downturn in the various economies of the world, developed and developing countries channels their energies on human capital development to accelerate their economic growth and sustainability in the development of their SME’s. It is on this note that this study arises to examine the effect of poor human capital development on the economic growth and sustainable development of small and medium enterprises in Aba, Abia state. The study used a primary source of data through questionnaire collected from the SME’s in Aba. The hypotheses were tested using Friedman 2 Way ANOVA and the results of the study show that poor education & skill acquisition programmes and poor health & medical facilities have significant effect on the economic growth and sustainable development of SME’s in Aba at 1% significant level. Thus, the study recommends for government active involvement in the provision of human capital development like education, health care, infrastructures and basic amenities to ensure peace, economic growth and sustainable development of the state.